Oxygen doped g‐C3N4 with nitrogen vacancy for enhanced photocatalytic hydrogen evolution. Issue 21 (23rd September 2020) - Tang, Hua; Xia, Zhihua; Chen, Ran; Liu, Qinqin; Zhou, Tianhua
Abstract: Generally, bulk graphic carbon nitride (g‐C3 N4 ) suffers from fast photogenerated charge carrier combination, inferior light absorption and insufficient active sites. Herein, we developed a defect engineering approach which can simultaneously realize O dopant and N defects in the g‐C3 N4 framework via an acid‐assisted thermal treatment route. The modified g‐C3 N4 demonstrated greatly enhanced photocatalytic H2 activity with a H2 evolution rate of 2.20 mmol ⋅ g −1  ⋅ h −1, which is more than three times higher than that of bulk g‐C3 N4 . The mechanism of the enhanced activity was investigated and proposed that the introduction of O dopants and N defects in the g‐C3 N4 could optimize the electron structure, up‐shift the conduction band, increase the surface area, and thus achieve more efficient separation of photogenerated carriers, stronger reduction ability and abundant active sites for photocatalytic H2 evolution. Thus, defect engineering has been demonstrated to be a prospective strategy to modify the performance of g‐C3 N4 for future photocatalytic energy generation. Abstract : An O‐doped g‐C3 N4 framework with abundant N defects was developed as a photocatalyst to boost photocatalytic hydrogen production.